2019
DOI: 10.32942/osf.io/yka3z
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Into the wild: microbiome transplant studies need broader ecological reality

Abstract: Gut microbial communities (microbiomes) profoundly shape the ecology and evolution of multicellular life. Interactions between host and microbiome appear to be reciprocal, and ecological theory is now being applied to better understand how hosts and their microbiome influence each other. However, some ecological processes that underlie reciprocal host-microbiome interactions may be obscured by the current convention of highly-controlled transplantation experiments. Although these approaches have yielded invalu… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…Thus, we used reciprocal transplants in the field to investigate the stability of the F . distichus microbiota in ecologically realistic conditions (Greyson‐Gaito et al ., 2020). Again, we found that existing differences by site of origin were resistant to change over the 6‐day experiment (Figs 3 and 4) and significant differences in microbiota by site of origin persisted.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, we used reciprocal transplants in the field to investigate the stability of the F . distichus microbiota in ecologically realistic conditions (Greyson‐Gaito et al ., 2020). Again, we found that existing differences by site of origin were resistant to change over the 6‐day experiment (Figs 3 and 4) and significant differences in microbiota by site of origin persisted.…”
Section: Discussionmentioning
confidence: 99%
“…distichus and the microbiota. Field‐based transplant studies are a crucial yet underutilized tool to understand host–microbiota associations in ecologically realistic conditions (Greyson‐Gaito et al ., 2020). We hypothesized that the microbiota of transplanted F .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Here we ruled out stress as a determining factor as baseline and stress-induced corticosterone did not explain PSP. Further manipulative experiments, such as using a wide range of food rewards, or microbial transplantation experiments 12 , 61 in the absence of dietary differences would provide additional support that the microbiome itself caused the change in problem solving performance.…”
Section: Discussionmentioning
confidence: 99%
“…First, a thorough understanding of the basic microbial ecology of animal systems that engage in natal philopatry is still lacking. Overall, microbiome research has been largely biased towards model systems and biomedical studies [122][123][124]. In many wild systems we still lack thorough knowledge on the routes of microbial acquisition, microbial sharing, and the effects of microbial communities on performance and fitness.…”
Section: Future Directionsmentioning
confidence: 99%